2023
DOI: 10.1021/acsnano.2c10623
|View full text |Cite
|
Sign up to set email alerts
|

Surface Defects Regulate the in Vivo Bioenergetic Response of Earthworm Eisenia fetida Coelomocytes to Molybdenum Disulfide Nanosheets

Abstract: Two-dimensional molybdenum disulfide (2D MoS2) nanomaterials are seeing increased use in several areas, and this will lead to their inevitable release into soils. Surface defects can occur on MoS2 nanosheets during synthesis or during environmental aging processes. The mechanisms of MoS2 nanosheet toxicity to soil invertebrates and the role of surface defects in that toxicity have not been fully elucidated. We integrated traditional toxicity end points, targeted energy metabolomics, and transcriptomics to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 72 publications
0
15
2
Order By: Relevance
“…Unlike P-NSMoS 2 , V-NSMoS 2 specifically induced membrane stress and mitochondrial motility processes. Sun et al demonstrated that surface defects induced by UV irradiation can enhance the in vivo bioenergetic toxicity of NSMoS 2 for earthworm coelomocytes, including stronger electron-transfer interference and ROS accumulation . The impacted biological pathway was verified by assaying cellular uptake at low temperatures (Figure C), demonstrating that the V-NSMoS 2 uptake is associated with energy consumption.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Unlike P-NSMoS 2 , V-NSMoS 2 specifically induced membrane stress and mitochondrial motility processes. Sun et al demonstrated that surface defects induced by UV irradiation can enhance the in vivo bioenergetic toxicity of NSMoS 2 for earthworm coelomocytes, including stronger electron-transfer interference and ROS accumulation . The impacted biological pathway was verified by assaying cellular uptake at low temperatures (Figure C), demonstrating that the V-NSMoS 2 uptake is associated with energy consumption.…”
Section: Resultsmentioning
confidence: 98%
“…Coelomocyte viability significantly decreased to 84.0, 76.0, and 82.1% of the control following 24 h of in vitro exposure to 50 μg of Mo/mL P-NSMoS 2 , V-NSMoS 2 , and ionic Mo, respectively (Figure B). The cellular uptake of nanomaterials is thought to be an initiating event of cytotoxicity. , Our previous work reported the oxidative stress and energy metabolism disturbance in the coelomocytes as part of the overall response of earthworms upon in vivo exposure to NSMoS 2 and that vacancy defects enhanced such toxicity potential . However, it is challenging to track the real-time interaction of NSMoS 2 with coelomocytes in vivo , thus hampering the effort to establish a mechanistic connection between the observed toxicity and cellular uptake behavior.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations